Umowa o ponoszenie opłat za pobyt w domu pomocy społecznej w orzecznictwie sądów administracyjnych - Pierzchała, Ewa (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
This paper is devoted to the issue of concluding an agreement on the charges for staying at a nursing home in the case law of administrative courts. The debated issue is based on a very extensive case law and against this background the most important problems are discussed. The first problem concerns the sources and forms of participation in the cost of maintaining a person in a social welfare home. In the case law of administrative courts a prevailing view is that law is the source. Other opinion says that the source is an administrative decision. The second opinion cannot be accepted. The views in the case law of the courts tend to conclude that the source of the duty is the law and the agreement individualizes this obligation. Another issue concerns the refusal to conclude an agreement on participation in the cost of maintaining a person in a social assistance home. In this situation, in the case law a prevailing view is that an agreement may be replaced with a central administrative decision.
Keywords: umowa administracyjna; decyzja administracyjna; prawo; pomoc społeczna; dom opieki; orzecznictwo sądów administracyjnych